Assessment of the efficiency of ColiSureâ„¢ for coliforms Escherichia coli enumeration in pasteurizad milk - Beloti, Vanerli; Barros, Márcia de Aguiar Ferreira; Nero, Luís Augusto; Santana, Elsa Helena Walter de; Souza, Juliana Aparecida de; Franco, Bernadette Dora Gombossy Melo (Semina: Ciências Agrárias, 2000)
<!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} p.Style1, li.Style1, div.Style1 {mso-style-name:Style1; margin:0cm; margin-bottom:.0001pt; text-align:justify; line-height:15.1pt; mso-line-height-rule:exactly; mso-pagination:none; mso-layout-grid-align:none; text-autospace:none; font-size:12.0pt; font-family:Arial; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} span.FontStyle16 {mso-style-name:"Font Style16"; mso-ansi-font-size:11.0pt; mso-bidi-font-size:11.0pt; font-family:Arial; mso-ascii-font-family:Arial; mso-hansi-font-family:Arial; mso-bidi-font-family:Arial;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> In the dairy industry the coliforms detection can he used as indicative of hygiene production of the raw milk and the contamination after-pasteurization. The traditional methods for the enumeration of the total and faecal coliforms are laborious and needs an incubation time of 96 hours. Rapid methods for detection of these microorganisms have been developed and among them the ColsSuroit is a rapid method that gives results in 24 hours and involves defined substrates for simultaneous determination of total conforms and E. coli in water based in specific enzymatic reactions of these microorganisms. The objective of this study was to evaluate its utilization in milk. Ninety-five samples of pasteurized milk were collected from the markets in Londrina city, Parana and analyzed by the Most Probable Number (NMP) enumeration using the Brilliant Green Bile Lactose Broth (BGBL) and ColiSure™. There was a correlation of 0.80 betwee-n the mediums when the incubation time was 43 hours for total conforms. The low down occurrence of E. coffin the analyzed samples made impossible to comparate the performance of methods for this microorganism. Compfementary analysis showed a greater sensibility and especifity of the ColiSure™ in comparation with the BGBL. The CofiSure™ can be indicated as a substitute for the traditional method, with the advantage to be faster and easier.